Efficacy of vigisox against main nematodosis at commission and field testing in cattle - I. A. Arkhipov; A. I. Varlamova; N. V. Danilevskaya; N. I. Koshevarov; E. E. Belova; K. M. Sadov (Российский паразитологический журнал, 2016)
In commission testing vigisox showed 100 % efficacy against gastrointestinal strongylatosis at the dose of 60 mg/kg bw in cattle. Efficacy of vigisox against tri- chocephalosis of cattle was 98,32 %. In field experiments vigisox showed 100 % efficacy against Nematodirus spp., 99,2 % against gastrointestinal strongylatosis of cattle.